La grande enfance - Jean-François Dupeyron (Éducation et Socialisation)
This text reviews on the representations of childhood in Occident, and points the inadequacies and the difficulties of the contemporary representation of the child as a subject. Thus, this representation provides today a real ‘scholarly rumour’ about the discovery of the childhood during the occidental modernity and constitutes the hard core of a paradigm. The critic of this paradigm comes along with several propositions to take a fresh look at the childish subjectivity, from the phenomenology of the childish life and with the support of Michel Henry’s and Georges Canguilhem’s works. So the French school shape is referred to a former orthopædic influence, which the current ‘pedagogy of the skills’ is extending: of this fact, the difficulties of the subjectivation of the child are interpreted as the consequences of a prevented activity. In fine, the model of a Great Childhood (Nietzsche) proposes a new philosophical horizon for the pedagogical welcoming of a form of life filled of acting power: the early chilhood.